HUTAN JATI BERKALUNG BESI: PENGANGKUTAN KAYU JATI DI JAWA PADA AKHIR ABAD KE-19 DAN AWAL ABAD KE-20 - Warto Warto (SASDAYA: Gadjah Mada Journal of Humanities, 2017)
Teak forests became one of the important resources in Java in the past. Teak forests did not only provide economic benefits for residents to fulfill their daily needs but also provided other benefits, especially in stabilizing the forest environment. However, the condition began to change when the teak forests exploited. In the 19th century and early 20th century, the environmental teak forests experienced degradation and deforestation that was difficult to control. The presence of teak logging companies at the end of the 19th century became the starting point of the accelerated deforestation. In running a business, they used modern tools that can simplify the process of harvesting and be transporting of teakwood. Some of the modern tools called trams and trains which were used to carry teak logs from the forests to shelters and ports. By utilizing modern transportation, teak woods can be transported quickly, accurately and massively. This paper shows that the opening of tram and train rail road’s in teak forests in addition to facilitating the transportation of goods and people, also led to the improvement and expansion of teak massive deforestation.